Pemodelan Angka Kematian Ibu (AKI) Di Indonesia Menggunakan Mixed Geographically Weighted Regression (MGWR) - Lawwamah, Tamsilul; Harsyiah, Lisa; Aini, Qurratul (Semeton Mathematics Journal, 2024)
Maternal Mortality Rate (MMR) is on of the targets for a  achieving the Sustainable Development Goals (SDGs). The aim of this research is to find the right model for estimating MMR and to look at the factors that influence MMR in Indonesia. Estimation were carried out using the Mixed Geographically Weigthed Regression (MGWR) model. The MGWR model is a combination of GWR and linear regression with variables that  having influence locally and some globally. The results obtained are that the MGWR model is superior the GWR model, because  the smallest AIC value for MGWR is 463,0564. Factors that have significant influence using the adaptive Gaussian kernel weighting are postpartum mothers (x4) , postpartum mothers receiving vitamin A (x5), giving Fe3 tablets to pregnant women (x6) ,  and handling obstetric complications (x7).